Some remarks on tile effect of dynamic absorber - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1989)
In order to limit the vibration of mass m2 (fig. 1) while the mass m1 is subject ted to a harmonic force Q0sinωt, the dynamic absorber can be used. In this case the  system considered is of more than two degrees of freedom. The article presented dealer with some linear systems of this kind with various methods of attaching the dynamic absorbers. It seams that advantageous absorbers are those given in figures 2 and 3. Whereas two absorbers acting simultaneously as shown in figs 4, 5, 6 do not give more effectiveness.